A comparative physicochemical and cosmetic evaluation of generic topical corticosteroid products - Widodo, Riyanto Teguh; Hashim, Hadida; Usir, Ezlina (Faculty of Medicine, University of Malaya, 2002)
Comparison and evaluation of physicochemical properties of the six betamelhasone'17-valer.. te creams available locally were studied. Tests that were conducted include stiffness/hardness, grittiness. colour, odour, homogeneity (phase separation), pH, weight of )OS5, tackiness (stickiness) and microscopic examination. A point grading system was used 10 assess and compare the products. Results revealed that Betnovale' and Camnovale' to be the most superior followed by Beavate', Setrosone', Belasone' and Uniflex'